Glycoproteomic profiling of serum-derived small extracellular vesicles enriched via ultracentrifugation and affinity-based techniques - Mojibola Fowowe; Cristian D. Gutierrez Reyes; Judith Nwaiwu; Joy Solomon; Oluwatosin Daramola; Sherifdeen Onigbinde; Joseph Andrew Whitley; Houjian Cai; Yehia Mechref (Scientific Reports)
Abstract Small extracellular vesicles (sEVs) are gaining recognition as potential biomarkers for diseases, including cancer, due to their involvement in key pathophysiological processes. However, the glycosylation of EVs and the specific roles of their glycans remain poorly understood. While several methods exist for isolating sEVs from complex biological samples, achieving sufficient purity and quantity for mass spectrometry-based glycoproteomic analysis remains a significant challenge. In this study, we compared two commonly used isolation methods, ultracentrifugation (UC) and immunoaffinity capture (MagCapture kit), across different starting volumes of human serum (200 µL and 500 µL) to evaluate their performance for downstream glycoproteomic analysis. While prior studies have examined protein content across isolation methods, our work uniquely investigates how isolation technique and sample volume affect glycoproteomic yield and quality. We show that UC, particularly at higher sample volumes, enables deeper glycoproteomic coverage, whereas MagCapture is advantageous when serum availability is limited. Notably, we report for the first time site-specific glycan microheterogeneity on sEV glycoproteins derived from human serum, including multiple glycoforms at the same glycosylation site. These findings highlight the complexity and biological relevance of glycosylation in sEV proteins and offer practical guidance for optimizing isolation protocols based on specific omics applications.